PENGARUH TRADISI “SONGGOT” TERHADAP PENDAPATAN PEDAGANG SEMBAKO DI KOTA TANJUNGBALAI - Asra Idriyansyah Purba; Lainatusshifa Kemal (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2023)
This study aims to provide an overview of the "Songgot" tradition in the people of Tanjung Balai, North Sumatra. The Tanjung Balai community is a pluralistic society that still holds the "Songgot" tradition for certain events. Therefore, this tradition needs logistics, in this case the food that must be provided. The focus of the problem that the author wants to convey in this research is the "Songgot" tradition, which, like the obligatory tradition in the Tanjung Balai community, requires the role of "sembako" traders for the nine basic commodities of society. Where everyone wants to make this tradition must be served food. The methodology in this study the authors use quantitative. Which performs data analysis with static procedures and systematic modeling and literature review analysis. The results of this study indicate that the "Songgot" tradition in the Tanjung Balai community has an influence on the income of traders in the Tanjung Balai city market. The traders in Tanjung balai have a significant impact on this tradition because their wares sell high with many people making this "Songgot" tradition event which affects the income of traders.